Similar serological response to conventional therapy for syphilis among HIV-positive and HIV-negative women. Issue 5 (October 1995) - Goeman, J; Kivuvu, M; Nzila, N; Behets, F; Edidi, B; Gnaore, E; Van Dyck, E; St Louis, M; Piot, P; Laga, M
Abstract : OBJECTIVES–To compare characteristics of syphilis serological reactivity in HIV positive (+) and HIV negative (-) female sex workers, as well as the serological response to therapy after treatment with intramuscular benzathine penicillin, 2.4 million U weekly, for three consecutive weeks. METHODS–Rapid plasma reagin (RPR) and Treponema pallidum haemagglutination assay (TPHA) results of 72 HIV-positive and 121 HIV-negative women reactive in both tests were assessed. The response to therapy was prospectively monitored with quantitative RPR serology in 47 HIV-positive and 73 HIV-negative patients. Cumulative probabilities of becoming nonreactive by RPR were compared at six months, one and two years after therapy. RESULTS–At enrolment, the geometric mean titres of RPR and TPHA were lower in HIV-positive patients (RPR, 1:2.6) than in HIV-negative patients (RPR, 1:3.8; p < 0.01). The evolution over time of RPR titres was similar among HIV-positive patients as compared to HIV-negative patients. Among patients with an initial RPR titre of < 1:8, 53% of HIV-positive and 44% of HIV-negative patients became RPR negative two years after therapy. Among patients with an RPR titre of 1:8 or greater at enrolment, 83% of HIV-positive and 90% of HIV-negative patients had reached at least a fourfold decline of RPR titres two years after therapy. CONCLUSIONS–Syphilis serology findings (both RPR and TPHA) may be altered in the presence of HIV infection, but the serological response to therapy was similar in HIV-positive and HIV-negative patients.